The Prevalence of Stunting, Poverty, and Economic Growth in Indonesia: A Dynamic Panel Data Causality Analysis - Kustanto, Andi (Journal of Developing Economies, 2021)
In recent years, policy discussions and debates have emphasised the efficiency of development policies to translate economic growth into sustainable economic development. One of the main aspects in this regard is achieving improvement in child nutrition through economic development. Nevertheless, there is a scarcity of literature that empirically verifies the causality between stunting, poverty, and economic growth in 34 provinces in Indonesia using Klassen's typology analysis and Panel VECM. This study indicates that the prevalence of stunting has a direct causality towards poverty and economic growth in the long-term by 0.02%. Handling high the prevalence of stunting needs to be focused on in all provinces in Indonesia. Poverty directly affects the stunting prevalence and economic growth in the long-term by 0.06%. The percentage of the population, poverty outside Java, including Nusa Tenggara, Moluccas, and Papua, is also higher than in Java. Therefore, efforts to tackle poverty should be more focused on these areas. Economic growth has a direct causality to the prevalence of stunting and poverty by 0.57%. It proves that the country's economic growth is accompanied by socioeconomic development and improving the poor's livelihoods and welfare. Can also recommend specific nutrition and sensitive nutrition interventions to impact the massive reduction of stunting in Indonesia. Keywords: Stunting, Poverty, Economic Growth, IndonesiaJEL: I10; I18; I32; O10; O15; P36